Makroravinteiden, hydrologian ja geomorfologian vaikutus kasvilajirunsauteen ja biomassaan subarktisessa ympäristössä - Vuollet, Johanna (Helsingfors universitet, 2012)
This thesis is motivated by the need for more knowledge about the factors which influence the plant species richness and biomass in subarctic and alpine environments. It is known that the effects of climate warming will be most severe in arctic, subarctic and alpine regions. A warmer climate will change the vegetation composition and biomass production in these environments. In this thesis I investigate the effects of six nutrients (Ca, Na, Mg, Fe, K and P), hydrological conditions early in the growing season and geomorphology on plant species richness and biomass in the northernmost part of Finland, Kilpisjärvi. The conditions in the study site are subarctic-alpine. In subarctic and alpine regions the varying topography in macro and micro scales leads to a wide variety of habitats even within small spatial dimensions. Materials in this study include field observations about the plant species richness and biomass, geomorphological processes and hydrological conditions; chemical analysis of soil samples; and topography variables derived from a digital elevation model. Methods used are generalized linear models and variation partitioning, which are both more and more used in ecological and geomorphological studies. The results suggest that the most influential of the environmental variables on the plant species richness and biomass is geomorphology. It is the most influential explanatory variable on total, vascular plant, bryophyte and lichen species richness as well as on total, bryophyte and lichen biomass. The amount geomorphology explains varies between 9 - 41 %. The variation in vascular plant species richness is best explained by hydrological conditions (14 %). The variables chosen for this study are able to explain over 50% of the species richness response variables. For total, bryophyte and lichen biomass the amount explained is about 20 - 47 %, and even 77 % of total biomass is explained by the variables. Geomorphology, hydrology and nutrients are able to explain better the variation in biomass than in ...